Physical aging of polymers of intrinsic microporosity: a SAXS/WAXS study - McDermott, Amanda G.; Budd, Peter M.; McKeown, Neil B.; Colina, Coray M.; Runt, James (Journal of materials chemistry. A, Materials for energy and sustainability, 2014)
Porosity in polymers of intrinsic microporosity (PIMs) is closely related to free volume: it arises from a chain structure combining rigid segments with sites of contortion, producing a large concentration of interconnected pores smaller than 1 nm. Membranes of these polymers are subject to physical aging, which decreases their permeability and reduces their performance in gas separation. In this work, a robust interpretation of PIM X-ray scattering features is developed with support from molecular dynamics simulations. The sensitivity of scattering patterns to time, temperature and film thickness is shown to be qualitatively consistent with physical aging, demonstrating that these high-free-volume, porous polymeric glasses present a unique opportunity to study structural changes during physical aging using scattering methods. Quantitative modeling of PIM scattering patterns remains challenging, and the time resolution required to capture the initial aging stages of a single film is difficult to achieve with laboratory instruments. However, the spectrum of glassy states accessed by varying film thickness and aging temperature raises the possibility that there may be two distinct mechanisms of aging in PIMs.